Pemikiran Pendidikan Islam dalam Perspektif Zakiah Daradjat - Al-Farabi, Mohammad; Hanum OK, Azizah; Nasution, M. Rifat Ibrahim (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
This study discusses Zakiah Daradjat's perspective on Islamic education and its contribution to Islamic education in Indonesia. The main issues discussed are: (1) The concept of Islamic education according to Zakiah Daradjat; (2) The contribution of Zakiah Daradjat's thoughts about Islamic education to Islamic education in Indonesia. This study used the library research method, with primary data sources obtained from the works of Prof. Dr. Zakiah Daradjat who focuses on 3 (three) books, namely Psychology, Islamic Education, and Religious Education in Mental Development, as well as secondary data sources in the form of books relevant to this research. The data analysis technique used by the author in this study is data triangulation. The results of the discussion concluded: the concept of Islamic education according to Zakiah Daradjat is the essence of forming human beings who have noble morals or in other words morals are good deeds. Morals are a reflection of faith in the form of behavior, speech, and attitude. Because Islamic education is not merely religious education, but the cultivation of a religious spirit by accustoming children to good qualities and habits. The goal of Islamic Education is the embodiment of Islamic values in the human person of the student that is endeavored by Muslim educators. The contribution of Islamic education thought initiated by Zakiah Daradjat can be seen theoretically, namely: The components of Islamic education according to him are educators, students, educational methods, and curriculum which are an inseparable unit, one with the other equally taking part in achieve the goal, namely to create a generation of good morals. In practice, he was a reformer of Islamic education in his day